The drop [large type] : a novel - Connelly, Michael, 1956- (Connelly, Michael, 1956- Harry Bosch series, 2011)
Detective Harry Bosch investigates a cold case and the murder of a city councilman's son. The cases are unrelated but they twist around each other like the double helix of a DNA strand. One leads to the discovery of a killer operating in the city for as many as three decades; the other to a deep political conspiracy that reached back into the dark history of the police department.